Young females at risk while driving with a small child. (November 2017) - Maasalo, Ida; Lehtonen, Esko; Summala, Heikki
Highlights: Analysis of characteristics and risk of crashes among female drivers with an infant passenger. Crashes involving infants typically occurred in ordinary driving conditions. Drivers with an infant passenger were more often fatigued or inattentive than drivers with no passengers. Young females are at an elevated risk of fatal crashes when driving with an infant passenger. An adult passenger in addition to an infant passenger lowered drivers' risks regardless of the driver's age. Abstract: Introduction: Previous research suggests that young mothers with little driving experience are at risk when driving with a small child passenger. In this study we examined the prevalence, characteristics and risk of fatal motor vehicle crashes involving an infant passenger under the age of one among female drivers of different ages. Methods: We used crash data from the US Fatality Analysis Reporting System for 1994–2013. The prevalence of fatal crashes involving infants was examined by age of female drivers and compared to the number of births among mothers of a similar age. The essential characteristics of the crashes were described, and the odds of being at fault were determined for young (16–24-year-olds) and older female drivers (25–39-year-olds) with an infant passenger or with no passengers. Results: The prevalence of fatal crashes involving infant passengers was higher among young female drivers in relation to the number of births among mothers of a similar age than among older females. Young female drivers with an infant passenger were more often at fault than older drivers (aOR = 1.83, 95%, CI = 1.52, 2.20). Their vehicles were older and smaller and they used proper safety seats for infants less often than the older drivers. In addition, young female drivers with an infant passenger but with no adult passenger in the vehicle were more often at fault than young female drivers with no passengers (aOR = 1.27, 95% CI = 1.06, 1.51). Both young and older female drivers' crashes involving an infant passenger typically occurred in ordinary driving conditions, but these drivers with infant passengers were more often reported as having fallen asleep or inattentive than those with no passengers. The presence of an adult passenger in addition to an infant passenger lowered female drivers' odds of being at fault, regardless of the driver's age. Conclusions: Young females driving with an infant passenger, probably most often mothers, are at an elevated risk of a fatal crash, especially when they drive alone with an infant. The protective effect of an adult passenger suggests that another adult in the vehicle can assist the driver by taking care of the infant and enabling the driver to focus on driving.